2004
DOI: 10.1111/j.1475-1313.2004.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between injected volume and optical parameters in refilled isolated porcine lenses

Abstract: The correlation found between the refilling volume and the lens power (0.04 mL D(-1)), as well as the correlation between the lens thickness and the lens power (0.54 mm D(-1)), might be important factors to be controlled in conjunction with surgery, as these also determine the lens power in the presence of this refill material. An increasing lens filling volume is associated with decreasing accommodative amplitude. The positive spherical aberration of refilled porcine lenses presents a sharp contrast to the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
0
18
1
Order By: Relevance
“…Although the polymer lenses were flatter and smaller than natural rabbit lenses, this did not result in a significantly higher radius of curvature of the anterior and posterior surfaces. Contrary to findings in porcine lenses ex vivo reported by Nishi et al 19 and Koopmans et al 21 (who achieved lens refilling of between 95% and 140% of the natural lens volume), the volume of the refilled lenses in our study was consistently found to be significantly lower than that of the natural crystalline lenses. During injection of the refilling material, the surgeon does not receive feedback on the amount of filling achieved other than that the injected polymer is present in the whole pupillary area.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the polymer lenses were flatter and smaller than natural rabbit lenses, this did not result in a significantly higher radius of curvature of the anterior and posterior surfaces. Contrary to findings in porcine lenses ex vivo reported by Nishi et al 19 and Koopmans et al 21 (who achieved lens refilling of between 95% and 140% of the natural lens volume), the volume of the refilled lenses in our study was consistently found to be significantly lower than that of the natural crystalline lenses. During injection of the refilling material, the surgeon does not receive feedback on the amount of filling achieved other than that the injected polymer is present in the whole pupillary area.…”
Section: Discussioncontrasting
confidence: 99%
“…The 7.1 T MRI proved to be useful in visualizing the amount of lens refilling; however, due to the long measuring times, the method would be too cumbersome to use intraoperatively. Because the amount of lens refilling affects the total refraction of the eye and may be related to the amplitude of accommodation obtained, 19,21 it is important to be able to monitor this parameter. New technologies are therefore required to optimize the intraoperative refilling procedure by measuring the refraction of the eye being refilled or by measuring lens geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Koopmans and co-workers (Groningen, Netherlands) created a laboratory set-up that allows study of the shape and refraction response of natural and refilled lenses under circumferential stretching through the ciliary body and zonular complex and found the power changes of refilled lenses to be comparable with the young natural lens [32]. They found that an increase in thickness of the relaxed lens by 0.54 mm resulted in a 1-D increase in power in refraction, whereas overfilling decreased the amount of lens power change [34]. They also learned that when using an adequate bottle height during refilling and a plug for capsulorhexis closure, lens dimensions similar to the natural lens could be achieved [33].…”
Section: "Lens Refilling"mentioning
confidence: 99%
“…Numerous treatments for presbyopia have been developed; unfortunately, none of these approaches offers all of the benefits of the natural mechanism of accommodation. Therefore, efforts have been made to replace the aged lens with a biomimetic substitute matching the behavior of the natural lens using a process called ''lens refilling'' (Kessler, 1964;Koopmans et al, 2003;Koopmans et al, 2006;Koopmans et al, 2004;Parel et al, 1986;.…”
Section: Introductionmentioning
confidence: 99%